FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN MAHASISWA MEMILIH PROGRAM STUDI EKONOMI SYARIAH PADA FAKULTAS AGAMA ISLAM UNIVERSITAS SILIWANGI - Lina Marlina; Fatimah Zahra Nasution (Universitas Siliwangi, 2019)
This research aims to analyze the variables influence the student’s decisions in choosing Islamic Economics Department of Islamic Religion Faculty in Siliwangi Univesity at Tasikmalaya and to know the variables give significant influence. This research used a quantitative approach based on cross section obtained through the techniques of data collection with the dissemination of a questionnaire to 189 students as respondents. The data was collected then to be tabulated, done coding then analyzed by statistical tools with computer software or Statistical Package for Social Science (SPSS 20.0) 20.0. Using data in this study is significantly complied qualify the normality of the data. The results of this study indicated by value R2 of 0.838 with high value F count (85.998) than F table (0.95;5;183) or 2.26 so H0 is rejected. This means that there is a linear relationship between independent and dependent variables. It can also be seen from the significance (0.000) α (0.05) so H0 is rejected. This study explained that there is a significant linear relationship between the independent variables (facilities, the lecturers, job opportunities, costs and reputation campus) with dependent variable. This show that 84% of the entire influence factors are tested simultaneously to the decision significantly